2015
DOI: 10.1007/s10067-015-2941-y
|View full text |Cite
|
Sign up to set email alerts
|

Clinical associations of anti-Smith antibodies in PROFILE: a multi-ethnic lupus cohort

Abstract: The aim of this study was to determine the association of anti-Sm antibodies with clinical manifestations, comorbidities, and disease damage in a large multi-ethnic SLE cohort. SLE patients (per American College of Rheumatology criteria), age ≥16 years, disease duration ≤10 years at enrollment, and defined ethnicity (African American, Hispanic or Caucasian), from a longitudinal US cohort were studied. Socioeconomic-demographic features, cumulative clinical manifestations, comorbidities, and disease damage (as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
36
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(46 citation statements)
references
References 44 publications
5
36
0
Order By: Relevance
“…Baseline anti-Smith positivity was also associated with complete peripheral depletion. Anti-Smith is the most specific antibody in SLE and has been associated with more severe features and poor outcomes (38)(39)(40). It is unclear why this association was found, but if it were to be reproduced in subsequent studies then further investigation into the relationship would be warranted.…”
Section: Discussionmentioning
confidence: 99%
“…Baseline anti-Smith positivity was also associated with complete peripheral depletion. Anti-Smith is the most specific antibody in SLE and has been associated with more severe features and poor outcomes (38)(39)(40). It is unclear why this association was found, but if it were to be reproduced in subsequent studies then further investigation into the relationship would be warranted.…”
Section: Discussionmentioning
confidence: 99%
“…Anti-Smith (anti-Sm) antibodies is a highly speci c autoantibody in SLE, directly against seven Smith proteins that constitute the small nuclear ribonucleoprotein particles [21,22]. Besides acting as a SLE classi cation criterion, anti-Sm antibody has been found to be related with speci c subsets of system involvements [23] and disease activity [24]. In terms of skin manifestation, previous research revealed that anti-Sm antibody was associated with photosensitivity, malar rash and discoid rash [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study using genetic admixture in Hispanics, having a higher proportion of Native American ancestry was found to be associated with severe diabetic retinopathy, alluding to the possible genetic effect on diabetes’ manifestation . Studies of systemic lupus erythematous have also identified an increase in autoantibody reactivity in non‐Whites, leading to shifts in the understanding that genetically determined ancestry is involved in the biological processes that increase lupus prevalence and disease severity. Thus, we propose that future studies should incorporate multiethnic cohorts and genetic ancestry to better address markers of disease process in both ON and MS.…”
Section: Discussionmentioning
confidence: 99%